FAMILY EDUCATION IN A MALAY CULTURAL PERSPECTIVE - Kaspullah (Journal of Islamic, Social, Economics and Development, 2019)
In the concept of Islam through the information of Al-Quran and Hadith kaffah in expressing the urgency of family education, which aims for the benefit or sustainability of human life better. However, on the other hand massive globalization impacts affect every aspect of human life. Not infrequently informed abused (abused) in the form of violence against children by parents themselves. Parents or families in this context who are supposed to be a place for development and protection for children turn into inhospitable institutions. In addition, in the modern family life should be the husband as a partner for the wife in building a harmonious family (sakninah), but the reality there are many cases of domestic violence (Domestic Violence) dominated by the husband. Taking into account the phenomenon of domestic violence, it is necessary to populist thinking by offering the concept of representative family education so as to be an alternative to modern families today. One of them is by offering family education model by accommodating local culture. This is based on the assumption that every region, tribe, has its own peculiarities to build a harmonious family. The family education perspective of Malay culture in particular is based on the noble values of Malay culture which are still preserved by parents up to now, which are internalized in the goals, programs, methods, and assessment of family education.